Implementasi Kerja Sama Mukhabarah dan Muzara’ah dalam Meningkatkan Kesejahteraan Petani Padi di Desa Benteng Rendah - Rosi Dwi Seftianti; Titin Agustin Nengsih; G. W. I Awal Habibah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This thesis discusses the implementation of the mukhabarah and muzara'ah system to improve the welfare of rice farmers in Benteng Bawah village, Mersam sub-district, Batanghari district, Jambi province. The main issues raised are how to implement the mukhabarah system for rice farming, how to implement the muzara'ah system for rice farming in Benteng Bawah Village, what is the impact of implementing the mukhabarah and muzara'ah system for agricuture on the economic welfare of rice farmers in Benteng Bawah Village.This type of research includes qualitative research, to obtain valid data the researcher uses data collection methods, namely observation, interviews and documentation. The data sources in this research are primary and secondary. The data analysis technique used is crosswel. Available data, which is usually in the form of a telephone call, is analyzed. This part of the analysis usually involves data classification. The resuts of research on the implementation of the mukhabarah and muzara'ah systems to improve the welfare of rice farmers in Benteng Bawah village, Mersam sub-district, Batanghari district, Jambi province, namely, in the mukhabarah system the harvest is divided into 3 parts, where 2 parts are for sharecroppers and 1 part is for land owners, because all costs and seeds are paid by the land cutivator, whereas in the muzara'ah system the harvest is divided into two or equally because the seeds and costs are paid by the land owner. These two systems have an impact on the welfare of land owners and sharecroppers, enough to meet food needs until the next harvest.